PERENCANAAN BANGUNAN PENGAMAN PANTAI (REVETMENT) DENGAN BAHAN GEOBAG DI PANTAI MASCETI, KABUPATEN GIANYAR - I Kadek Sandi Wiguna Putra; Cok Agung Yujana; Nyoman Surayasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT Bali has area of 5634.4 km2 with a relatively high population density of 576 people / km2. The length of coastal areas in Bali reaches 633.35 km long which is currently in crisis condition. Approximately 215.82 km of coastal areas in Bali experience predicted erosion due to high waves, coastal sediment mining, construction of beach arching infrastructure, and construction of inappropriate beach structures. Gianyar regency has a beach length of 14.28 km, of which 10.48 km of it is eroded, and the average erosion rate is 3.202 m/year. To anticipate the erosion of the progressive planning revetment is expected to be able to withstand and absorb the pressure of the wave that occurs, so as to overcome erosion in Masceti Beach. Data is one of important things in design process. These data include: 10 years of wind data, topographic data and bathymetry, and tidal data. Then the data is analyzed to obtain the dominant wind direction that occurs at the planning site, the plan wave height and the elevation height of the revetment Based on the analysis results can be taken that the dominant wind comes from the southeast that is equal to 35.96%, with the largest speed is 10 knots or 8.65 m/s. The maximum wave height with a 25-year re-use of the Gumbel (H25) method is 0.913 m, the inner wavelength (L0) is 27.720 m and the wave velocity (C0) is 6,580 m/s and the plan wave height (H0) is 0.784 m. The breaking wave height (Hb) is 0.7108 m with the breaking wave depth (db) is 0.7545 m and the water level of the plan plan (DWL) is 1.43 m calculated from the MSL or Â± 0.00. The height of the revetment building is 3.3138 m with a peak width of 1.12693 m and the thickness of the revetment safety wall layer is 1.12693 m and the weight of the geobag as a protective plywood is 0.2866 tons. The height of the foot protector for the revetment building is 1.12693 m with a width of 2.352 m Keyword: revetment, masceti, erosion, wave